2014
DOI: 10.4184/asj.2014.8.6.820
|View full text |Cite
|
Sign up to set email alerts
|

Operative Technique forEn BlocResection of Upper Cervical Chordomas: Extended Transoral Transmandibular Approach and Multilevel Reconstruction

Abstract: Anterior exposure for cervical chordomas remains challenging because of the anatomical complexities and the restoration of the dimensional balance of the atlanto-axial region. In this report, we describe and analyze the transmandibular transoral approach and multilevel spinal reconstruction for upper cervical chordomas. We report two cases of cervical chordomas (C2 and C2-C4) that were treated by marginal en bloc resection with a transmandibular approach and anterior-posterior multilevel spinal reconstruction/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…The purpose of surgical management of upper cervical intraspinal tumors is to resect the tumor, relieve spinal cord compression, and restore spinal stability. 3 , 12 Various surgical approaches have been described for the treatment of upper cervical intraspinal tumors, including an extreme lateral approach, 13 , 14 an anterior approach, 15 , 16 and a posterior approach. 17 , 18 However, the ideal surgical approach for upper cervical intraspinal tumors located in the ventral cervical cord is still controversial because of the complicated anatomic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of surgical management of upper cervical intraspinal tumors is to resect the tumor, relieve spinal cord compression, and restore spinal stability. 3 , 12 Various surgical approaches have been described for the treatment of upper cervical intraspinal tumors, including an extreme lateral approach, 13 , 14 an anterior approach, 15 , 16 and a posterior approach. 17 , 18 However, the ideal surgical approach for upper cervical intraspinal tumors located in the ventral cervical cord is still controversial because of the complicated anatomic structure.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy in this region is highly complex and involves many critical neurovascular structures that must be preserved to maintain the patient’s post-operative functional status. The transoral approach, which was originally pioneered by Kanavel in 1917, allows for midline access to a wider surgical field with access to multiple cervical vertebrae from C1 to C4 with less compromise to key neurovascular structures [22,23]. This approach has been used in the past to access the anterior cervical spine as noted by Tuite et al in their report on 27 pediatric patients with occipitocervical junction pathology [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that the transmandibular approach provided wide access to C3–4 caudally. [ 17 ] The authors also described that glossotomy was necessary when the lesion extended to C2 and below and that the cosmetic deformity and functional loss were minimal despite the seemingly radical incision.…”
Section: Discussionmentioning
confidence: 99%